2020
DOI: 10.2147/jpr.s223092
|View full text |Cite
|
Sign up to set email alerts
|

<p>A Step Towards a Better Understanding of Pain Phenotypes: Latent Class Analysis in Chronic Pain Patients Receiving Multimodal Inpatient Treatment</p>

Abstract: Purpose: The number of non-responders to treatment among patients with chronic pain (CP) is high, although intensive multimodal treatment is broadly accessible. One reason is the large variability in manifestations of CP. To facilitate the development of tailored treatment approaches, phenotypes of CP must be identified. In this study, we aim to identify subgroups in patients with CP based on several aspects of self-reported health. Patients and Methods: A latent class analysis (LCA) was carried out in retrosp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 59 publications
0
19
0
Order By: Relevance
“…Similarly, a recent study reported that subgroups of patients with varying levels of affective pain experiences reported analogous levels of depressive difficulties. For sensory pain experiences, by contrast, respective mappings appeared more heterogeneous [ 66 ]. No changes in coping attitudes were observed.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a recent study reported that subgroups of patients with varying levels of affective pain experiences reported analogous levels of depressive difficulties. For sensory pain experiences, by contrast, respective mappings appeared more heterogeneous [ 66 ]. No changes in coping attitudes were observed.…”
Section: Discussionmentioning
confidence: 99%
“…In a first effort for phenotyping, a recent study used an analogous data-driven approach to identify multiple patterns of hearing loss in tinnitus patients [ 83 , 84 ]. Analyses using LCA on chronic pain patients revealed four classes separated by the severity of pain and affective symptoms [ 85 ]. While this previous work suffers from the limitations imposed by small datasets and a limited focus on the comorbid conditions, it delivers a data-driven proof of concept that a phenotyping approach is feasible.…”
Section: Identification Of Phenotypesmentioning
confidence: 99%
“…In addition to such biomarkers, psychological markers are promising to understand complex phenotypes such as chronic pain. Using latent class analyses, Obbarius et al [ 85 ] demonstrated that depression, anxiety, and physical health were markers for the burden of pain. What is currently missing is an overarching approach combining biomarkers and psychosocial markers spanning comorbid disorders.…”
Section: Conclusion: System Medicine Approaches—a Change From Classic...mentioning
confidence: 99%
See 1 more Smart Citation
“…Others, evaluating chronic or acute patient cohorts, also identified patterns of response to treatment. 2,5,[10][11][12]20 Thus, finding patterns of outcomes seems to be typical of patients in pain. However, the number and characteristics of the subgroups might be cohort specific, and they are not necessarily generalizable to other settings, for example, from pain clinic to primary care or across countries.…”
Section: Seeking Out "Patterns" Of Responses Among a Population Of Pa...mentioning
confidence: 99%